End web stiffeners for connecting ductile replaceable links. (November 2018) - Stephens, Max T.; Dusicka, Peter; Lewis, Gregory
Abstract: The ability to restore the integrity of structural lateral systems that utilize steel links to inelastically deform in earthquakes can be improved through the use of replaceable links. Replaceable links can be removed when damaged, especially when isolated from the gravity carrying system, and can provide engineers greater design freedom with respect to structural stiffness and strength. To ensure that ductile inelastic deformation is isolated to the effective length of the replaceable link, robust connection details capable of sustaining large cyclic deformations are needed. An integrated numerical and experimental research program was performed to evaluate a bolted end plate connection detail which utilized fillet welds, instead of full joint penetration welds, between the links and end plates in an effort to simplify fabrication. Continuum finite-element methods were used to evaluate various end stiffener options to shift flange plastic strains caused by link deformation away from the welds. The results from that study informed the selection of cases evaluated in large-scale experiments. Cyclic pseudostatic tests were conducted to experimentally demonstrate the performance of the selected end-stiffener configurations. Results from the experimental investigation showed that ductile inelastic deformation within the effective length of the links can be achieved using a bolted end plate connection with fillet welds between the shear link and end plate by utilizing end stiffeners placed parallel to the web. Design recommendations for incorporating the end stiffeners are outlined based on the data and experiences gained. Highlights: A bolted end plate connection which uses stiffeners to increase ductility is introduced for replaceable links in EBF. Non-linear models are used to demonstrate a wide range of stiffener configurations. Experiments demonstrate that selected end stiffener configurations increase the deformation capacity of the link. Design recommendations for incorporating the end stiffeners are outlined.